The Sustainability of Carbon Mitigation in Dryland Farming Systems: The Oil Mallee Case Study - Dawkins, Simon (Curtin University, 2020)
This thesis identifies social and technical influences that diminished the capacity of carbon forestry to play a more significant role in reducing carbon emissions in Australia. A case study of the Oil Mallee project in the Western Australian Wheatbelt is used to highlight the difficulties of transitioning from innovation to wide adoption.